2013
DOI: 10.21528/lnlm-vol11-no1-art3
|View full text |Cite
|
Sign up to set email alerts
|

RB: A New Method for Constructing Multi-Label Classifiers Based on Random Selection and Bagging

Abstract: In many real world prediction problems, a classifier must, or should, assign more than one label to an instance, e.g. prediction of machine failures, musical genre classification, etc. For this kind of problem, multi-label classification methods are needed. One approach frequently used to learn multi-label predictors divides the problem into one or more multi-class classification problems, and combines the models constructed for each sub-problem to classify new instances with multiple labels. Although there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Correlation between the results and Card, as well as between the results and Dens, was expected. However, as we explain later in this section, we observed that many situations where correlations were observed in [5] could not be observed in our results. We also calculated Spearman's rank correlation between Card and each measure results, and also was calculated between Dens and each measure results using (i) only natural datasets; and (ii) only MSD-based datasets.…”
Section: Experiments Results and Analysiscontrasting
confidence: 59%
See 4 more Smart Citations
“…Correlation between the results and Card, as well as between the results and Dens, was expected. However, as we explain later in this section, we observed that many situations where correlations were observed in [5] could not be observed in our results. We also calculated Spearman's rank correlation between Card and each measure results, and also was calculated between Dens and each measure results using (i) only natural datasets; and (ii) only MSD-based datasets.…”
Section: Experiments Results and Analysiscontrasting
confidence: 59%
“…We present the results obtained for MSD-based datasets. We also bring to this work the results obtained for the six datasets used in [5] to enrich our analysis, and we also enlarge that results to evaluate similarly to the evaluation using MSD. We analyze the relation between (i) cardinality and (ii) density and the results obtained by each method.…”
Section: -71 2014mentioning
confidence: 96%
See 3 more Smart Citations